Remaking the obsolete: Critical geographies of contemporary adaptive reuse. Issue 1 (16th December 2021) - Lynch, Nicholas
Abstract: Adaptive reuse, the repurposing of buildings for new uses, is an age‐old practice designed to reimagine, remake and revitalize local economies, cities and communities. In more recent decades, reuse has become part of a systematic process of contemporary city building and a globalized practice of placemaking. As such adaptive reuse is much more that a technical or practical application but is rather a complex process that engages with and transforms the social, cultural and spatial dynamics of cities and their communities around the world. This article focuses on the contemporary geographies of adaptive reuse and highlights three key themes: reuse in the post‐industrial city, reuse on the 'edges' and 'peripheries' of the global built environment, and reuse as part of the global sustainability discourse. Overall, this review highlights the rich and growing research across urban, cultural and environmental geography and exposes a number of ways in which this process operates as a powerful tool in shaping local and regional contexts.